A Multi-Platform GUI for Circuit Schematic Design Using CircuiTikZ - Pfannenmüller, Christof; Wiedemann, Jan Philipp Wiedemann; Kirzinger, Manuel; Weigel, Robert (Latin America Microwave Conference, 2025)
The powerful CircuiTikZ-package provides typesetting of electrical and electronic networks and is commonly used in all areas of electrical engineering. The TikZ-based syntax is powerful, but unintuitive and tedious, leading to a lot of time used for creating the schematic drawings. A browser-based graphical user interface (GUI) is presented that provides features such as "what you see is what you get" (WYSIWYG). The presented browser application lets the user design the circuitry graphically. The tool calculates the component positions based on user input and exports (Circui)TikZ code for use in Latex like typesetting documents significantly speeding up the circuit schematic drawing proces